2019
DOI: 10.1094/pdis-10-18-1857-re
|View full text |Cite
|
Sign up to set email alerts
|

Virulence, Molecular Diversity, and Mating Type of Curvularia lunata in China

Abstract: Curvularia leaf spot (CuLS), caused by Curvularia lunata, is a devasting foliar disease in the maize-growing regions of China. Resistant varieties were widely planted in these regions in response to CuLS. However, over time, C. lunata has gradually adapted to the selective pressure and, in recent years, the incidence of CuLS has increased. To assess the correlation between virulence and genetic diversity, a total of 111 isolates was collected from 15 maize-growing regions located in nine provinces in China. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Moreover, comparative transcriptome analysis of low-virulence and high-virulence C. lunata strains revealed that host pressure increased pathogen virulence by increasing the pathogen’s biosynthesis of toxins and melanin. , To prevent disease re-epidemics in maize-growing areas, more attention should be given to the dynamic changes of strains with varied virulence. The combination of different molecular approaches and biochemical methods could be applied to monitor pathogenic variation. , Additionally, C. lunata can produce many virulence factors, but the synthesis mechanisms of these factors, such as toxin and melanin, are still not clear. Therefore, further exploration of the precursors, intermediates, and node genes involved in virulence factor synthesis is required to propose corresponding effective methods to control C. lunata infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, comparative transcriptome analysis of low-virulence and high-virulence C. lunata strains revealed that host pressure increased pathogen virulence by increasing the pathogen’s biosynthesis of toxins and melanin. , To prevent disease re-epidemics in maize-growing areas, more attention should be given to the dynamic changes of strains with varied virulence. The combination of different molecular approaches and biochemical methods could be applied to monitor pathogenic variation. , Additionally, C. lunata can produce many virulence factors, but the synthesis mechanisms of these factors, such as toxin and melanin, are still not clear. Therefore, further exploration of the precursors, intermediates, and node genes involved in virulence factor synthesis is required to propose corresponding effective methods to control C. lunata infection.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical and molecular identification techniques have also been utilized to differentiate the virulence of C. lunata isolates. Isozymes, random amplified polymorphic DNA (RAPD), universally primed PCR (UP-PCR), internal simple sequence repeat (ISSR), and amplified fragment length polymorphism (AFLP) methods have also been tested to analyze the genetic variability among C. lunata strains. ,,,,− The classifications using one method or a combination of two or more methods were found to correlate with the classifications achieved using the differential host system method. Thus, biochemical and molecular identification methods have been used to assist the differential host system method in classifying the virulence of C. lunata .…”
Section: Virulence Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Virulence on maize leaves was scored with a disease index (Zhang et al ., 2019). After the investigation of disease index, the lesion number was statistically analysed and the length and width of at least 50 lesions were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Supplemental lighting was used at 25–50 klux (325–650 μE m −2 s −1 ) with 14 h light and 10 h night. Disease severity was evaluated as described (Zhang et al ., 2019). The length and width of brown infected areas were measured as the lesions size at the indicated time using Image J software.…”
Section: Methodsmentioning
confidence: 99%